Multiple AUVS for coastal oceanography - João Sousa (1997)
This paper presents the recent developments of the project Multiple Autonomous Underwater Vehicles for Coastal Oceanography, of the University of Porto. The project envisages the development of a highly operational and low-cost system for scientific and environmental data collection in the Portuguese coastal waters. The project activities suggested the development of a Generalized Vehicle (GV) Control Architecture for multiple vehicles. Reconfigurability, reliability and operational effectiveness, are at the basis of this control architecture, which encompasses human intervention besides the cooperation among AUVs and other system devices. A simulation environment was developed in SHIFT, to support the design and testing of the GV control architecture. SHIFT is a new specification language for describing dynamic networks of hybrid automata, which constitute the most adequate formalism for this problem domain.